2021
DOI: 10.3390/catal11070831
|View full text |Cite
|
Sign up to set email alerts
|

Green Synthesis, Structural Characterization and Photocatalytic Applications of ZnO Nanoconjugates Using Heliotropium indicum

Abstract: In recent years, biosynthesized zinc oxide nanoparticles (ZnO NPs) have been gaining importance due to their unique properties and tremendous applications. This study aimed to fabricate ZnO NPs by using extracts from various parts of the traditional medicinal plant Heliotropium indicum (H. indicum) and evaluate their photocatalytic activity. Further, their potential in photoluminescence and fluorescence resonance energy transfer (FRET) was assessed. The Ultraviolet-Visible spectrum exhibited a hypsochromic shi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(22 citation statements)
references
References 69 publications
0
22
0
Order By: Relevance
“…The synthesized pristine and Se/ZnO NPs were confirmed by several characterization techniques routinely used [ 15 , 25 , 26 , 27 , 28 ]. The first confirmation was done by UV-Vis spectrophotometry from UV-2800 BMS Biotechnology Medical Services, Madrid, Spain, spectrophotometer.…”
Section: Methodsmentioning
confidence: 99%
“…The synthesized pristine and Se/ZnO NPs were confirmed by several characterization techniques routinely used [ 15 , 25 , 26 , 27 , 28 ]. The first confirmation was done by UV-Vis spectrophotometry from UV-2800 BMS Biotechnology Medical Services, Madrid, Spain, spectrophotometer.…”
Section: Methodsmentioning
confidence: 99%
“…SnO 2 NPs have been fabricated using physical and chemical methods such as laser ablation, the sol–gel method, spray pyrolysis, microemulsion, microwaves, electrochemical deposition, co-precipitation, and hydrothermal, sonochemical, solvothermal, and non-aqueous routes [ 20 , 30 , 31 ]. Importantly, the paucity of reports on the photodegradation of dyes with NiO NPs and SnO 2 NPs compared to TiO 2 NPs and ZnO NPs [ 7 , 13 , 14 , 18 , 21 , 22 , 32 ] justifies the present study.…”
Section: Introductionmentioning
confidence: 97%
“…Compared to the other alternatives, semiconductor-based photocatalytic degradation has been proven to be an efficient, rapid, economical, and environmentally friendly process [ 10 , 11 , 12 ]. The photocatalysis process obeys the basic principle of the advanced oxidation process (AOP) to generate reactive radical species with UV radiation to catalyze organic pollutant degradation [ 7 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have demonstrated that green synthesis has gained a lot of popularity since it can produce NPs with superior morphological, photochemical, photocatalytical, and electrochemical properties compared to physiochemical synthesis. This method has become one of the preferred methods for synthesizing ZnO nanoparticles [ 13 ]. Similarly, BSA (bovine serum albumin)-silver nanoparticles are potentially promising candidates for treating skin cancer in a multimodal manner [ 14 ].…”
Section: Introductionmentioning
confidence: 99%